2022
DOI: 10.3390/children9030359
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the COVID-19 Pandemic on Children and Adolescents: Cognitive and Emotional Representations

Abstract: The present research investigated children and adolescents’ explicit and spontaneous representation of the COVID-19 pandemic and their related emotions, cognitions, and coping strategies. We explored the self-reported protective factors and coping mechanisms, in addition to similar attributional emotional experiences, i.e., the ways participants evaluated others’ pandemic experiences. Our sample consisted of 155 children and adolescents aged 10 to 13 (M = 10.70, SD = 0.85, 56.1% females). We designed a 12-item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Numerous studies have shown that the use of face masks during the COVID-19 pandemic has caused difficulties in children to adapt to them, problems of functional discomfort [ 10 ], compatibility with the use of glasses or breathing difficulties [ 26 , 36 ] and even psychological problems, such as anxiety or sadness [ 5 , 6 , 18 , 37 , 38 ]. Educators have warned about the negative influence that the use of facemasks has, in particular, on the proper development of children’s social life and their interaction with others [ 39 , 40 ], on the development of communication skills [ 13 , 21 ], on sound recognition and vocal self-perception [ 11 , 14 , 19 , 20 ], and on the development of speech skills [ 11 , 12 , 41 ]. This paper has analyzed the influence of the COVID-19 pandemic and, particularly, the use of facemasks, on the development of literacy objectives in early childhood education students, from the point of view of educators.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the use of face masks during the COVID-19 pandemic has caused difficulties in children to adapt to them, problems of functional discomfort [ 10 ], compatibility with the use of glasses or breathing difficulties [ 26 , 36 ] and even psychological problems, such as anxiety or sadness [ 5 , 6 , 18 , 37 , 38 ]. Educators have warned about the negative influence that the use of facemasks has, in particular, on the proper development of children’s social life and their interaction with others [ 39 , 40 ], on the development of communication skills [ 13 , 21 ], on sound recognition and vocal self-perception [ 11 , 14 , 19 , 20 ], and on the development of speech skills [ 11 , 12 , 41 ]. This paper has analyzed the influence of the COVID-19 pandemic and, particularly, the use of facemasks, on the development of literacy objectives in early childhood education students, from the point of view of educators.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate the need to support children, who will probably face similar emergencies later in life, in understanding SARS-CoV-2 and its resulting disease (Manches and Ainsworth, 2022). Consequently, it is essential to scaffold children's understanding of COVID-19 and assist them in coping with this unpredictable condition, to empower their responsible participation in mitigating the pandemic (Garcia de Avila et al, 2020;Provenzi et al, 2020;Maftei et al, 2022;Manches and Ainsworth, 2022;Rydström et al, 2022), and to prevent traumatic effects (Assante and Candel, 2020;Idoiaga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, despite the previously documented lack of appropriate understanding of infectious diseases and prevention practices in non-experts (Jee et al, 2015), recent studies report high levels of awareness of COVID-19 even in young children (Rydström et al, 2022), and their sensitivity in perceiving and adopting adults' reactions to the pandemic (Valadez et al, 2020;Thompson et al, 2021). This awareness has been revealed in children's ability to distinguish SARS-CoV-2 (cause) from ; to name common symptoms of the disease (for instance cough, fever, or sneeze); to understand the possibility of asymptomatic infection; to recognize the necessity of preventive and mitigation practices such as social distancing or handwashing; to describe airborne transmission and high contagiousness of the virus (Idoiaga et al, 2020;Bray et al, 2021b;Christidou et al, 2021;Martinerie et al, 2021;Thompson et al, 2021;Bonoti et al, 2022;Maftei et al, 2022;Rydström et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has abruptly changed the daily life of the global population, which has experienced repeated periods of social isolation with a sudden limitation of personal freedom and changes in the main dynamics of relationships. These difficult conditions have made the present historical period particularly critical for socio-emotional functioning, and especially for children, who are engaged in multifaceted developmental dynamics [ 1 ]. The lives of children and young people have been disrupted in many ways, as efforts to contain the pandemic have required the closure of many developmental contexts, such as schools, childcare centres, colleges, recreation centres, libraries, sport centres, and entertainment centres.…”
Section: Introductionmentioning
confidence: 99%